Determinants of food security: evidence from Ethiopian Rural Household Survey (ERHS) using pooled cross-sectional study - Kedir Hussein Abegaz (Agriculture & Food Security, 2017)
Abstract Background Though agriculture is obstructed by a number of both endogenous and exogenous problems, it is the dominant generator of means of livelihoods for the majority of people in the least developing countries like Ethiopia. The aim of this study is to look at the status of food security and to identify its determinants in the rural Ethiopia. Methodology The pooled data for this study were obtained from the sixth and seventh round of the Ethiopia Rural Household Survey (ERHS). Bar chart and frequency distribution tables were used to illustrate the given data. Binary multivariable logistic regression was employed to identify the determinants of food security. Results and conclusion Majority of the households were found to be food insecure, though the figure of food insecurity decreased in 2009 when it is compared with 2004. Food security was significantly determined by rain shock, lack of off-farm income, and region of the households. To assure food security, the farmers should have to consider every rain seasons in the farming activity and the availability of off-farm income-generating activities should have to be enhanced. Finally, there is a need for an international policy regarding the adoption of mitigation strategies to control climate change, the main cause of agriculture and rainfall shock.